2014
DOI: 10.1108/jadee-05-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Study of consumers’ behavior for non-vegetarian products in emerging market of India

Abstract: Purpose – The purpose of this paper is to understand non-vegetarian food consumption behavior, and factors affecting the same of the consumers of middle-sized market, where organized retailing is still at infancy. Design/methodology/approach – A total of 182 households of two middle-sized cities of India were personally surveyed with a structured questionnaire. Simple statistical analysis such as frequency distribution, factor analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…However, this willingness was dependent on the particular consumer segment and product category. Moreover, it has been found that Indians are price sensitive consumers (Kumar and Kapoor, 2014; Mukherjee et al , 2012) and they generally do not prefer to pay more for “green” attribute in a product (Khoiruman and Haryanto, 2017; Nasir and Karakaya, 2014; Dutta et al , 2008). In our study respondents also explicitly emphasized on the high prices of the green products, which deject them to buy eco-friendly products as they mentioned they had to manage their budget and compare to other products green products are highly rated like R4 mentioned “Green products are expensive like organic products are expensive […] as per my economic cost I don’t buy green products” and R17 stated “I don’t think prices of green products are justified.…”
Section: Methodsmentioning
confidence: 99%
“…However, this willingness was dependent on the particular consumer segment and product category. Moreover, it has been found that Indians are price sensitive consumers (Kumar and Kapoor, 2014; Mukherjee et al , 2012) and they generally do not prefer to pay more for “green” attribute in a product (Khoiruman and Haryanto, 2017; Nasir and Karakaya, 2014; Dutta et al , 2008). In our study respondents also explicitly emphasized on the high prices of the green products, which deject them to buy eco-friendly products as they mentioned they had to manage their budget and compare to other products green products are highly rated like R4 mentioned “Green products are expensive like organic products are expensive […] as per my economic cost I don’t buy green products” and R17 stated “I don’t think prices of green products are justified.…”
Section: Methodsmentioning
confidence: 99%
“…Average per capita consumption in the South Asia region is as low as 7 kg a year, while that of India is reported to be only about 4 kg annually. In general, meat products are not a part of regular diet for many Indian families, and non-vegetarian foods are considered as a special food for most of the consumers (Kumar & Kapoor, 2014). While globally, about 805 million people are estimated to be chronically undernourished in 2012-14, India still has the highest absolute numbers of undernourished people (Hossain, 2014), which necessitates the provision of alternative sources of nutrition such as meat products.…”
Section: Structural Changes In Global Meat Consumptionmentioning
confidence: 99%
“…In the given context, the first objective of this study deals with attitudinal factors affecting the attitude of Indian youth toward nutrition, which is of immense value for business, policy makers, and academics. Furthermore, food preferences and behavior are likely to vary from culture to culture (Akamatsu et al, 2005;Coveney, 2006;Falk, Sobal, Bisogni, Connors, & Devine, 2001) and are dependent on consumers' sociodemographic and economic characteristics (Brown et al, 2009;Kumar & Kapoor, 2014). There is a need to identify these differences (Chang, 2014) and the influences of consumers' characteristics (Aschemann-Witzel & Hamm, 2010;Drichoutis et al, 2007).…”
Section: Journal Of Food Products Marketingmentioning
confidence: 98%
“…The public are increasingly aware of the close association between food and health and are more willing to adopt healthier eating attitudes (Lappalainen et al, 1998). Consumers take more interest in nutrition, health, and quality aspects of the foods they consume and no longer seek to simply satiate their appetite (Gil et al, 2000;Kumar & Kapoor, 2014) The rising health consciousness around the globe has witnessed an era that emphasizes a healthier approach to life (Schreiner, Huyskens-Keil, Krumbein, Prono-Widayat, & Ludders, 2003).…”
Section: Introductionmentioning
confidence: 98%